Phenomenological Concept of Law from the Perspective of Carlos Cossio - Goździalski, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The originality of Cossio’s works is expressed by a strong relationship between philosophy of law and his philosophical assumptions. The starting point for deliberating on law are widely recognized ontological and epistemological contentions. Cossio justifies his legal theses basing them on his philosophical views. Egology derives from Edmund Husserl’s phenomenology which is related to some elements of William Dilthey’s philosophy of culture. Martin Heiddeger’s and Immanuel Kant’s philosophies are the basis too. The first part describes Cossio’s ontologies of subjects otherwise known as regional ontologies. Methods for examining the above subjects and gnoseological acts are presented here too. The second part presents the characteristics of law as a cultural subject. The article is not only a report. Its aim is also to show that Carlos Cossio’s legal philosophy is semantic in character.